Temporal Trends and Factors Associated with Bisphosphonate Discontinuation and Restart. (10th December 2019) - Adami, Giovanni; Jaleel, Ayesha; Curtis, Jeffrey R; Delzell, Elizabeth; Chen, Rui; Yun, Huifeng; Daigle, Shanette; Arora, Tarun; Danila, Maria I; Wright, Nicole C; Cadarette, Suzanne M; Mudano, Amy; et al.
ABSTRACT: Adverse events related to long‐term use of bisphosphonates have raised interest in temporary drug discontinuation. Trends in bisphosphonate discontinuation and restart, as well factors associated with these decisions, are not fully understood at a population level. We investigated temporal trends of bisphosphonate discontinuation from 2010 to 2015 and identified factors associated with discontinuation and restart of osteoporosis therapy. Our cohort consisted of long‐term bisphosphonate users identified from 2010 to 2015 Medicare data. We defined discontinuation as ≥12 months without bisphosphonate prescription claims. We used conditional logistic regression to compare factors associated with alendronate discontinuation or osteoporosis therapy restart in the 120‐day period preceding discontinuation or restart referent to the 120‐day preceding control periods. Among 73, 800 long‐term bisphosphonate users, 59, 251 (80.3%) used alendronate, 6806 (9.2%) risedronate, and 7743 (10.5%) zoledronic acid, exclusively. Overall, 26, 281 (35.6%) discontinued bisphosphonates for at least 12 months. Discontinuation of bisphosphonates increased from 1.7% in 2010, reaching a peak of 14% in 2012 with levels plateauing through 2015. The factors most strongly associated with discontinuation of alendronate were: benzodiazepine prescription (adjusted odds ratio [aOR] = 2.5; 95% confidence interval [CI] 2.1, 3.0), having a dual‐energy X‐ray absorptiometry (DXA) scan (aOR = 1.8; 95% CI 1.7, 2.0), and skilled nursing facility care utilization (aOR = 1.8; 95% CI 1.6, 2.1). The factors most strongly associated with restart of osteoporosis therapy were: having a DXA scan (aOR = 9.9; 95% CI 7.7, 12.6), sustaining a fragility fracture (aOR = 2.8; 95% CI 1.8, 4.5), and an osteoporosis or osteopenia diagnosis (aOR = 2.5; 95% CI 2.0, 3.1). Our national evaluation of bisphosphonate discontinuation showed that an increasing proportion of patients on long‐term bisphosphonate therapy discontinue medications. The factors associated with discontinuation of alendronate were primarily related to worsening of overall health status, whereas traditional factors associated with worsening bone health were associated with restarting osteoporosis medication. © 2019 American Society for Bone and Mineral Research.